2016
DOI: 10.1097/ccm.0000000000001713
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Based on Body Mass Index Is Associated With Morbidity and Mortality in Mechanically Ventilated Critically Ill Children in the PICU*

Abstract: Objective To determine the influence of admission anthropometry on clinical outcomes in mechanically ventilated children in the pediatric intensive care unit (PICU). Design Data from 2 multicenter cohort studies were compiled to examine the unique contribution of nutritional status, defined by BMI Z-score, to 60-day mortality, hospital-acquired infections, length of hospital stay, and ventilator free days (VFD), using multivariate analysis. Setting 90 PICUs from 16 countries with 8 beds. Patients Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
2
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 39 publications
(47 reference statements)
14
110
2
19
Order By: Relevance
“…This finding corroborates our decision to exclude the underweight patients, who have multiple independent risk factors for a worse prognosis, from this study. In addition, Bechard et al 26 reported that although obese patients had a higher rate of hospital-acquired infections, there was no difference in mortality risk or length of mechanical ventilation in the overweight or obese group compared with normal-weight patients, which is a finding similar to the results of this study. Finally, Ward et al 13 looked at the impact of obesity on the outcomes in pediatric patients with acute respiratory distress syndrome (ARDS).…”
Section: Discussionsupporting
confidence: 89%
“…This finding corroborates our decision to exclude the underweight patients, who have multiple independent risk factors for a worse prognosis, from this study. In addition, Bechard et al 26 reported that although obese patients had a higher rate of hospital-acquired infections, there was no difference in mortality risk or length of mechanical ventilation in the overweight or obese group compared with normal-weight patients, which is a finding similar to the results of this study. Finally, Ward et al 13 looked at the impact of obesity on the outcomes in pediatric patients with acute respiratory distress syndrome (ARDS).…”
Section: Discussionsupporting
confidence: 89%
“…Admission z scores based on weight for age and BMI for age (or weight for length for children <2 years) in relation to population reference standards have been used to classify patients as undernourished or obese. Admission BMI z scores predicted mortality in a large multicenter cohort of children receiving mechanical ventilation 4 . Due to the consistent associations with LOS, duration of mechanical ventilation, and mortality, BMI z scores may be useful to screen for patients at risk of poor outcomes in the PICU 17 .…”
Section: Introductionmentioning
confidence: 97%
“…Since the first pediatric critical care nutrition guidelines (ASPEN) published in 2009, there has been a substantial increase in research and publications related to this subject. The impact of nutrition status and nutrient delivery during critical illness has been demonstrated on clinical outcomes such as mortality, infectious complications, and LOS 4 10 . Thus, careful planning and monitoring of nutrient delivery at the bedside is attempted in most intensive care units (ICUs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter cohort study reported BMI and outcomes in 1622 mechanically ventilated children; underweight and obesity were associated with a higher risk of hospital‐acquired infections and a lower likelihood of hospital discharge. In addition, underweight children had a higher risk of mortality and fewer ventilator‐free days 71 …”
Section: Assessment Of Body Composition and Protein Turnover During Cmentioning
confidence: 99%